Evaluasi Atas Penerapan Pernyataan Standar Akuntansi Keuangan 101 Dalam Kaitannya Dengan Kewajaran Penyajian Laporan Keuangan Pada PT. Bank Jabar Banten Syariah - Sutarti, Sutarti; Budianto, Enjang Tachyan; Saesar, Adilah (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2012)
Banking industries which run their business based on sharia principles strarted formally in 1992 and growing rapidly until today. Society and all sorts of sides related to sharia banks have a high trust to sharia banks to carry out their functions and they will require qualified accounting as a responsibility. In connection with presenting and arranging of qualified and transparent financial account (financial statement) in business, Indonesia Accountants Union (IAI) has a commitment to reach it by issuing PSAK No. 101. The purpose of this study is to evaluate the application of PSAK No. 101 concerning presentation worthiness of financial account at Sharia Bank. The evaluation was conducted to find out whether financial account presentation at Sharia Bank is in accordance with applicable accounting standard, the PSAK No. 101. The study was done at Bogor Branch Office of PT Bank Jabar Banten Shariah located in Jl. Pajajaran, Bogor. Data used by the author is the financial account of PT Bank Jabar Banten Shariah 2010. The result shows that financial accounting presented at PT Bank Jabar Banten Shariah has not been fully in mutual accord with PSAK No. 101, because no agrrement in using several terminologies which are not in mutual accord with PSAK 101.